A DESAIN E-MODUL BERTEMA SRAWUNG PASAR TAMBAK DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI ARITMATIKA SOSIAL - Kalista Devi Kumalasari; Martyana Prihaswati; Rohmat Suprapto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematics teaching materials used by teachers in learning are still in the form ofprinted books, namely LKS (Student Worksheets) and textbooks. As a result,students feel that the learning process is boring and monotonous. Therefore, it isimportant to have innovative forms of teaching materials integrated with technologyto make learning more interactive and increasingly accessible. This study aims todesign an e-module with the theme of Srawung Pasar Tambak using a GuidedInquiry Learning Model on valid Social Arithmetic material. This study uses theResearch and Development (RnD) research method with the ADDIE developmentmodel limited to the development stage. Data analysis techniques used includeneeds analysis, validation analysis of material experts and media experts. Thisstudy produced an e-module design along with e-module validation results frommedia experts with an average score of 3.9, categorized as very valid, and materialexperts with an average score of 3.9, categorized as very valid. The averagecombined e-module assessment from media experts and material experts obtaineda score of 3.9, categorized as very valid. This indicates that the e-module design issuitable for testing with students during the learning process.